An attempt to assess the results of air temperature measurements from automatic weather stations in comparison to glass thermometer measurements in the context of weather types - Urban, Grzegorz (Bulletin of Geography. Physical Geography Series, 2015)
In the article, an attempt to evaluate results on air temperature measurements with the use of automatic weather stations (AWS) and glass thermometers was undertaken. The analysis considered the aspect of atmospheric circulation. On the basis of simultaneous measurements carried out with the use of AWS and glass thermometers, accuracy of the measurements for 6 synoptic stations of IMGW-PIB was assessed. The stations represented the Lower and Opole Silesia regions. Mean differences in mean monthly and seasonal air temperature values (T) between AWS and glass results are not high. They are equal to ±0,1°C, rarely reaching -0,2°C. In cold season and in particular months as well, they are negative. On an annual scale the differences hardy ever occur. No connection between mean difference for mean air temperature and atmospheric circulation was found. The values of mean differences for mean monthly and seasonal maximum air temperature (Tx) are equal to ±0,1°C (except Śnieżka). The differences for T and Tx can be characterized by a low significance, within the normal range. Mean differences for mean monthly and seasonal minimum air temperature (Tn) are usually positive. In warm season they can reach 1,1°C. In the case of most of considered stations, for positive differences for Tn, an increase in average (+0,1°C ÷ +0,5°C) and high (+0,5°C ÷+1,0°C) differences is noticed. The only exceptions are Śnieżka and Opole stations. The differences for each category are not regular, therefore no universal corrections can be implemented.